2021
DOI: 10.3389/fphar.2021.767947
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Structures, Bioactivities and Structure-Function Analysis of the Polysaccharides From Safflower (Carthamus tinctorius L.)

Abstract: Safflower (Carthamus tinctorius L.) is a herbal plant with a long history of clinical application worldwide, such as coronary heart disease, hypertension, dysmenorrhea and amenorrhea. It is also extensively used as an important oilseed plant for hundreds of years in some countries, like China, India, Mexico and the United States. Therefore, safflower is believed as a crop with dual values of medicine and economy as well. Safflower polysaccharides (SPS), from the plant, are believed as one of the most important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…Safflower ( Carthamus tinctorius L.) is an herbal plant in the family of Compositae , which is cultivated extensively in Central Asia [ 1 , 2 ]. In the traditional medicine of many Asia countries, safflower is primarily used to alleviate joint pain, dysmenorrhea, amenorrhea, postpartum abdominal pain, and blood stasis by promoting blood circulation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Safflower ( Carthamus tinctorius L.) is an herbal plant in the family of Compositae , which is cultivated extensively in Central Asia [ 1 , 2 ]. In the traditional medicine of many Asia countries, safflower is primarily used to alleviate joint pain, dysmenorrhea, amenorrhea, postpartum abdominal pain, and blood stasis by promoting blood circulation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the traditional medicine of many Asia countries, safflower is primarily used to alleviate joint pain, dysmenorrhea, amenorrhea, postpartum abdominal pain, and blood stasis by promoting blood circulation [ 1 ]. Modern pharmacological studies have proved that safflower has multiple biological effects, such as antioxidation, antiinflammation, antitumor, and immunomodulatory [ 2 ]. These biological effects are closely related to the bioactive components in safflower, such as polysaccharides, pigments, alkaloids, flavonoids, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carthamus tinctorius, also known as safflower, plants that are native in many countries with dry and barren climates, has been used empirically in many diseases, including in respiratory diseases such as whooping cough and chronic bronchitis [14], [15]. The previous animal studies had five shown that Hydroxysafflor Yellow A (HSYA), a bioactive compound of C. tinctorius, may promote an anti-inflammatory state in afflicted tissues by boosting anti-inflammatory cytokines and M2 macrophages (an anti-inflammatory phenotype) [16], [17], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…41,42 In China, the flowers of safflower are widely used in Chinese herbal preparations due to their antioxidant, anti-inflammatory and antimicrobial properties, and they contain vitamins A and E, polyunsaturated fatty acids, linoleic acid, and other biologically active substances in large quantities. 43–46 The progression of some diseases like myopia (especially in children), trachoma, senile cataracts, symptoms of depression, cardiovascular disease and skin tumors have been successfully retarded by safflower or its mixtures with other herbs. 47,48 On the basis of its ingredients and medicinal effects, safflower has been used to fabricate bioactive AgNPs.…”
Section: Introductionmentioning
confidence: 99%